KOMERSIALISASI BUDAYA DALAM KONTEKS KESENIAN KUDA LUMPING (STUDI PADA PAGUYUBAN KRIDO TURONGGO MULYO) DI DESA TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Miarso, Adi; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is entitled "Cultural Commercialization in the Context of Lumping Horse Art (Study in the Krido Turonggo Mulyo Circle) in Tarai Village, Build Mine District in Kampar Regency". The study was conducted in Tarai Bangun Village, Tambang Sub-District, Kampar Regency, which aims to find out the community profile on the Krido Turonggo Mulyo Horse Arts and the form of commercialization at the Seni Kuda Lumping Krido Turonggo Mulyo association. The method used in this research is Descriptive Qualitative research method, namely the discussion of this research is presented and analyzed in the form of a description of the words (descriptions) with a qualitative approach. This research is also supported by the implementation of in-depth interviews with informants (informants) that have been determined in advance by researchers. So from the results of the interview obtained information that is very supportive for the validity of the data that became the focus of this research. Based on the results of research in the art of Krido Turonggo Mulyo lumping horse, uniqueness and change has been found from time to time and has been able to establish a good relationship by being able to collaborate with one of the motorized vehicle products, namely Yamaha. Among the uniqueness is that there were found six members of the Batak and Minang horse lumping arts community totaling six people, one Minang tribe, then five Batak tribes. These changes can be seen in the possession aspect experienced by dancers who once looked terrible now are more entertaining and humorous. The collaboration with Yamaha is meant to carry out cooperative relations aimed at producing economy and services. So this is the form of commercialization between lumping horse art and Yamaha, even though the contract is in the form of (verbal). Keywords: Commercialization, Profile, and  Lumping Horse Art